North American Borders in Comparative Perspective - Konrad, Victor A.; Correa-Cabrera, Guadalupe (Book collections on Project MUSE., 2020)
"North American Borders in Comparative Perspective provides a balanced and comparative view of borders in the diverse and dynamic region formed by Canada, the United States, and Mexico. The authors argue that North America is "not a level playing field for trade, migration, and other forms of exchange." In addition to traditional national and regional boundaries, the borders in North America are "increasingly based on wealth, race, education, and politics." By examining North America with a comparative perspective, the authors reveal "the distinctive nature of i) the over-portrayed Mexico-US border, and ii) the largely overlooked Canada-US border.""--